Visual Outcome following Blunt Ocular Trauma among Patients attended Tobruk Medical Center - Ensaf Abdeljawad; Naeima Elzalitni (AlQalam Journal of Medical and Applied Sciences, 2024)
Ocular trauma is a significant public health issue that leads to blindness and disability, especially in underdeveloped nations. It represents 5% of hospitalizations and one-third of cases with notable vision impairment, The objective of this study was to assess the visual effects of blunt trauma in order to provide valuable information for the development of future care regimens. The study was a longitudinal investigation carried out at Tobruk Medical Center. It encompassed all patients admitted to the ophthalmology department with different forms of ocular trauma from January to December 2023. The study demonstrated a significant association between trauma type and visual outcome severity [P<0.001], with blunt penetrating trauma having the greatest percentage of blind outcomes [63.6%]. The majority of eye injuries resulted in normal or mild vision impairment [74.1%], with only a tiny fraction leading to blindness [7%]. Visual outcomes are influenced by factors such as the nature of the trauma, the initial visual result, and the type of surgery performed. Effective supervision is essential for achieving the best possible visual results. Additional research is required to enhance the effectiveness of treatment strategies. تعتبر الصدمات العينية مشكلة صحية عامة مهمة تؤدي إلى العمى والإعاقة، خاصة في الدول المتخلفة. وهو يمثل 5% من حالات الاستشفاء وثلث الحالات التي تعاني من ضعف ملحوظ في الرؤية، وكان الهدف من هذه الدراسة هو تقييم التأثيرات البصرية للصدمة الحادة من أجل توفير معلومات قيمة لتطوير نظم الرعاية المستقبلية. كانت الدراسة عبارة عن تحقيق طولي تم إجراؤه في مركز طبرق الطبي. وقد شملت جميع المرضى الذين تم إدخالهم إلى قسم طب العيون والذين يعانون من أشكال مختلفة من الصدمات العينية في الفترة من يناير إلى ديسمبر 2023. وأظهرت الدراسة وجود ارتباط كبير بين نوع الصدمة وشدة النتائج البصرية [P <0.001]، مع وجود إصابة حادة مخترقة بأكبر نسبة من حالات المكفوفين. النتائج (63.6%). أدت غالبية إصابات العين إلى ضعف عادي أو معتدل في الرؤية (74.1%)، مع جزء صغير فقط يؤدي إلى العمى (7%). تتأثر النتائج البصرية بعوامل مثل طبيعة الصدمة والنتيجة البصرية الأولية ونوع الجراحة التي يتم إجراؤها. يعد الإشراف الفعال أمرًا ضروريًا لتحقيق أفضل النتائج البصرية الممكنة. هناك حاجة إلى مزيد من البحث لتعزيز فعالية استراتيجيات العلاج.